PENGARUH TINGKAT KEPADATAN KANDANG CLOSED HOUSE TERHADAP KONSUMSI DAN KONVERSI PAKAN AYAM BROILER STRAIN COBB - Mustika, Tisha Bunga; Ismoyowati, Ismoyowati; Samsi, Muhamad (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose of this research was to study the effect of closed house stocking density level on feed consumption and conversion cobb broiler chickens. Materials and Methods. The material used in this study was 200 unisex cobb broiler chickens. Cobb broiler chickens were reared for 34 days and harvested at 5 weeks of age. The research materials consisted of S-00 booster feed which was given to broiler chickens in the early pre-starter period of 0-10 days, S-11 feed was given at the age of 11-21 days in the starter period, and S-12G feed was given at the age of 22 days until harvesting in the finisher period from the production of PT Charoen Pokphand Indonesia. Feed and drink were given with measure adlibitum at 06.00; 11.00; 16.00; 21.00. The research was conducted using experimental methods based on a completely randomized design (CRD). The treatments used was closed house stocking density which consisted of 5 treatments: T1 = 8 chickens / m2; T2 = 9 chickens / m2; T3 = 10 chickens / m2; T4 = 11 chickens / m2; T5 = 12 chickens / m2, each treatment replicated 4 times. The variables measured were consumption and feed conversion. The data obtained were analyzed using analysis of variance. Results. The results of the analysis of variance showed that stocking density had no significant effect (P> 0.05) on the consumption and feed conversion of Cobb broiler chickens at week 4 and week 5. Average feed consumption for the fourth week at P1 (1087.59 ± 32, 83), P2 (1081.38 ± 22.39), P3 (1066.70 ± 42.63), P4 (1090.27 ± 16.21), P5 (1069.95 ± 14.21), while the average feed consumption in the 5th week on P1 (987.31 ± 52.18), P2 (961.11 ± 36.78), P3 (933.17 ± 43, 45), P4 (948.56 ± 64.46), P5 (970.79 ± 42.53). Conclusion. The conclusion of this study was that stocking density with an area of ​​8-12 chicken / m2 gave relatively the same response to consumption and feed conversion.